Epigenomic priming of immune genes implicates oligodendroglia in multiple sclerosis susceptibility - Meijer, Mandy; Agirre, Eneritz; Kabbe, Mukund; van Tuijn, Cassandra A.; Heskol, Abeer; Zheng, Chao; Mendanha Falcão, Ana; Bartosovic, Marek; Kirby, Leslie; Calini, Daniela; Johnson, Michael R.; Corces, M. Ryan; et al. (Neuron (Cambridge, Mass.), 2022)
Multiple sclerosis (MS) is characterized by a targeted attack on oligodendroglia (OLG) and myelin by immune cells, which are thought to be the main drivers of MS susceptibility. We found that immune genes exhibit a primed chromatin state in single mouse and human OLG in a non-disease context, compatible with transitions to immune-competent states in MS. We identified BACH1 and STAT1 as transcription factors involved in immune gene regulation in oligodendrocyte precursor cells (OPCs). A subset of immune genes presents bivalency of H3K4me3/H3K27me3 in OPCs, with Polycomb inhibition leading to their increased activation upon interferon gamma (IFN-γ) treatment. Some MS susceptibility single-nucleotide polymorphisms (SNPs) overlap with these regulatory regions in mouse and human OLG. Treatment of mouse OPCs with IFN-γ leads to chromatin architecture remodeling at these loci and altered expression of interacting genes. Thus, the susceptibility for MS may involve OLG, which therefore constitutes novel targets for immunological-based therapies for MS. [Display omitted] •Chromatin priming of immune genes in OLG in homeostasis and disease•BACH1, STAT1, and Polycomb involved in IFN-γ-mediated immune gene regulation in OPCs•MS susceptibility SNPs overlap with open chromatin regions in OLG•IFN-γ leads to altered chromatin and gene expression at SNP loci in mouse OPCs Meijer, Agirre, et al. show that mouse and human oligodendroglia present open chromatin at immune genes and MS susceptibility single-nucleotide polymorphisms in homeostasis and disease. Transcriptional activation of these open chromatin regions involves transcription factors such as BACH1 and STAT1 and changes in histone modification deposition and chromatin architecture.